2019
DOI: 10.1017/jns.2019.11
|View full text |Cite
|
Sign up to set email alerts
|

Addition of milk fat globule membrane-enriched supplement to a high-fat meal attenuates insulin secretion and induction of soluble epoxide hydrolase gene expression in the postprandial state in overweight and obese subjects

Abstract: CVD and associated metabolic diseases are linked to chronic inflammation, which can be modified by diet. The objective of the present study was to determine whether there is a difference in inflammatory markers, blood metabolic and lipid panels and lymphocyte gene expression in response to a high-fat dairy food challenge with or without milk fat globule membrane (MFGM). Participants consumed a dairy product-based meal containing whipping cream (WC) high in saturated fat with or without the addition of MFGM, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 53 publications
2
6
0
Order By: Relevance
“…The addition of MFGM to a meal high in saturated fat was also found to modify the postprandial insulin response and offered protection for those individuals with higher baseline Chol:HDL (Beals et al . 2019). Baars et al .…”
Section: Nutritional and Health Benefits Of Mfgmmentioning
confidence: 99%
“…The addition of MFGM to a meal high in saturated fat was also found to modify the postprandial insulin response and offered protection for those individuals with higher baseline Chol:HDL (Beals et al . 2019). Baars et al .…”
Section: Nutritional and Health Benefits Of Mfgmmentioning
confidence: 99%
“…A test in overweight and obese subjects showed that there existed a positive association between plasma phospholipids (indicative of full‐fat dairy consumption) and insulin sensitivity . Addition of MFGM to a high‐fat meal mitigated insulin secretion in the postprandial state in obese subjects, which indicates the potential role of MFGM in improving insulin response …”
Section: Discussionmentioning
confidence: 99%
“…37 Addition of MFGM to a high-fat meal mitigated insulin secretion in the postprandial state in obese subjects, which indicates the potential role of MFGM in improving insulin response. 38 BAT generates heat through UCP1, while excess WAT accumulation causes adipocyte hypertrophy. 39 Thus, pharmacological or dietary interventions facilitating the recruitment of brown fat cells or browning of WAT might be a new strategy for obesity therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated a significant relationship between food intake and sEH, including a study using an sEH in vivo activity marker (diol/epoxide ratios) that showed sEH was significantly reduced after rats ate diets with various potassium levels [ 16 ]. Another study found EPHX2 mRNA expression to be increased in overweight/obese individuals after eating a meal high in fat [ 17 ]. Several other studies using animal models have observed that a high-fat diet is associated with sEH upregulation, while a low-fat diet may lower sEH levels [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%